PELATIHAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) UNTUK GURU SEKOLAH DASAR - Ulfa, Maria; Awan Asri, Sri; Hasanah, Nur (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of technology and information cannot be avoided because it is related to the development of the nation and state. The development of technology and information is very influential on the education sector. Traditional teaching habits and teacher apathy in dealing with advances in technology and information have a negative impact on students. This condition was experienced by teachers at SD Negeri Bintara III Bekasi City when carrying out online learning during the COVID-19 pandemic. The absence of procedures when online learning is applied by schools makes teachers carry out learning only using WhatsApp group media with the assignment method. In fact, teachers should be able to use advances in technology and information to carry out learning in order to be able to facilitate their students to learn. The purpose of this training is to strengthen knowledge about Technological Pedagogical Content Knowledge (TPACK) and its application in learning in elementary schools. The training activities were carried out face-to-face at SD Negeri Bintara III Bekasi City for 3 days. The training activities not only provide theory about TPACK, but also provide practice on making TPACK-based learning videos using smartphones.